Who is al-Muhāğir ad-Dāġistānī, the Copyist of Mushaf of Fadil-Pasha ŠErifović? - Popara, Haso (Prilozi za orijentalnu filologiju, 2017)
By now many researchers of our cultural heritage have written about the Mushaf of Fadil-pasha Šerifović, which is being kept in Gazi Husrev-bey’s library in Sarajevo under the no. Ms. 12 and which was reproduced in phototypic edition in 5000 copies in the printing-house Yıldız in Istanbul, in 2002, but none of them has determined the name of the caligrapher al-Muhāğir ad-Dāġistānī, who completed his copy in 1265/1849. godine. Based on the available sources and literature, notes of the copyist in the manuscript of Mushaf and iğāza which was given in 269/1853 to Fadil-pasha Šerifović by shaikh of nakshibandi sufi order aš-šayḫ Yāsīn aš-Širwānī ad-Dāġistānī, it can be claimed with certainty that the copyist of Mushaf of Fadil-pasha Šerifović was Aḥmad ibn Muḥammad al-Muhāğir ad-Dāġistānī al-Makkī, who is a descendant of Prophet Muhammad's grandson Husain. He is the writer of the work Mubayyin ādāb tilāwa al-Qur’ān, whose autograph is being held in the library al-Asad (former Dār al-kutub aẓ-Ẓāhiriyya) in Damascus under the no. 6136. The copy was finished on 20th rağab 1287 (16th October 1870) in Makka, where he was a permanent resident. Among the inhabitants of Makka he was known under the nickname al-Muhāğir ad-Dāġistānī. He dedicated his work to the Ottoman sultan Abdulaziz (ruled 1861-1876). From the original of Fadil-pasha’s iğāza it can be seen that this al-Muhāğir ad-Dāġistānī was the teacher of Fadil-pasha’s teacher aš-šayḫ Yāsīn aš-Širwānī and that he was the shaikh of nakshibandi order in Makka, and that his teacher was aš-šayḫ ‘Abdulḥamīd aš-Širwānī, who wrote numerous works in Arabic. Although there is no information on the place of the copying of Mushaf of Fadil-pasha Šerifović, it can be suggested, according to the place of residence of the copyist al-Muhāğir ad-Dāġistānī, that it could be Makka.